Stigmatization of the patients and their relatives in alcohol and other substance dependencies - Arıkan, Zehra; Genç, Yasin; Etik, Çetin; Aslan, Selçuk; Parlak, İlkcan (Journal of Dependence, 2004)
Objective: Alcohol and substance dependence (except tobacco in many countries) frequently appears as moral devaluation, weakness of personality, personality disorder, and criminal liability. The stigmatization of alcohol and substance dependent persons is also observed in our country. According to our experiences the stigmatization can not be changed easily. We conduct this study to get some information about patients’ and their families’ difficulties in community.Method: We examined 100 patients and their 41 relatives who are over 18. These patients are diagnosed with alcohol dependency according to DSM IV and treated in Gazi University Medical Faculty Psychiatry Clinic, Alcohol Dependency Department. We developed two different questionnaires which have 27 questions each. These questionnaires contained items about alcohol and substance dependency. In addition, some items are related to community attitudes and prejudices about alcohol and substance dependency. These questionnaires contained both demographic information and questions about prejudice for alcohol and substance dependency. Some items were selected from phrases used by patients during treatment to describe their illness. Each item is evaluated by using chi square tests. Items have been differentiated and grouped related with personality features, moral values and patient’s insight about the illness. This grouped items also evaluated as statistical outcomes separately. Same evaluations have been applied to patients’ families. Findings are shown in tables.Results: Stigmatization rating of the patients are similar to stigmatization rating of the families. The relatives of the patients accept dependency as a personality problem more than the patients. Increased number of hospitalizations have changed patients’ view about substance dependency and reduced stigmatization as a moral problem. Both patients and families show differences on marital status; that married patients have more insight towards their illness than single patients. In addition, higher education level of the patients and their families is associated with reduced stigmatization. Patients living in the cities attribute a higher moral connotation to substance dependence. Alcoholics and their families consider substance dependency to be more related to personality problems and moral deficiency than alcoholism is. Therefore alcoholics may stigmatize substance abusers and discriminate as a different dependency group.Conclusion: This result may be related to concepts learned during hospitalization. Patients admitted through different channels may change their biases but these do not disappear completely.
Keywords: Stigmatization; alcohol dependence; substance dependence